Expanding conceptualizations of harm reduction: results from a qualitative community-based participatory research study with people who inject drugs - Boucher, L. M; Marshall, Z.; Martin, A.; Larose-Hébert, K.; Flynn, J. V; Lalonde, C.; Pineau, D.; Bigelow, J.; Rose, T.; Chase, R.; Boyd, R.; Tyndall, M.; et al. (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background The perspectives of people who use drugs are critical in understanding why people choose to reduce harm in relation to drug use, what practices are considered or preferred in conceptualizations of harm reduction, and which environmental factors interfere with or support the use of harm reduction strategies. This study explores how people who inject drugs (PWID) think about harm reduction and considers the critical imperative of equity in health and social services delivery for this community. Methods This community-based participatory research study was conducted in a Canadian urban centre. Using a peer-based recruitment and interviewing strategy, semi-structured qualitative interviews were conducted by and with PWID. The Vidaview Life Story Board, an innovative tool where interviewers and participant co-construct a visual “life-scape” using a board, markers, and customized picture magnets, was used to facilitate the interviews. The topics explored included injection drug use and harm reduction histories, facilitators and barriers to using harm reduction strategies, and suggestions for improving services and supports. Results Twenty-three interviews with PWID (14 men and 9 women) were analysed, with a median age of 50. Results highlighted an expanded conceptualization of harm reduction from the perspectives of PWID, including motivations for adopting harm reduction strategies and a description of harm reduction practices that went beyond conventional health-focused concerns. The most common personal practices that PWID used included working toward moderation, employing various cognitive strategies, and engaging in community activities. The importance of social or peer support and improving self-efficacy was also evident. Further, there was a call for less rigid eligibility criteria and procedures in health and social services, and the need to more adequately address the stigmatization of drug users. Conclusions These findings demonstrated that PWID incorporate many personal harm reduction practices in their daily lives to improve their well-being, and these practices highlight the importance of agency, self-care, and community building. Health and social services are needed to better support these practices because the many socio-structural barriers this community faces often interfere with harm reduction efforts. Finally, “one size does not fit all” when it comes to harm reduction, and more personalized or de-medicalized conceptualizations are recommended.